2020
DOI: 10.1002/jemt.23519
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of surface roughness after staining of different composite resins using atomic force microscopy and a profilometer

Abstract: Aim The aim of this study was to compare the surface roughness of different composite resins using atomic force microscope (AFM) and a profilometer after storage in different solutions. Materials and methods Eight different composite resins were used in this study. Twenty specimens of each composite resin material were prepared using a 2‐mm thick and 8‐mm diameter stainless steel mold. After the composites had been placed in the mold, they were polymerized with a LED curing unit. The surfaces of all specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…However, microhybrid composites investigated in the present study showed smoother surfaces than the nanohybrid composite. Although the following outcome is not in accordance with Karatas, Gul, Gündoğdu, and Iskenderoglu's (2020) and Sang, Song, Chung, Jin, and Hyun's (2021) studies, it could be attributed to the surface area/volume ratio of fillers which is a parameter that could increase the water uptake and matrix deterioration of the resin materials (Ilie & Hickel, 2009). Furthermore, EBF had lower surface roughness values among all bulk‐fill composite groups.…”
Section: Discussionmentioning
confidence: 74%
“…However, microhybrid composites investigated in the present study showed smoother surfaces than the nanohybrid composite. Although the following outcome is not in accordance with Karatas, Gul, Gündoğdu, and Iskenderoglu's (2020) and Sang, Song, Chung, Jin, and Hyun's (2021) studies, it could be attributed to the surface area/volume ratio of fillers which is a parameter that could increase the water uptake and matrix deterioration of the resin materials (Ilie & Hickel, 2009). Furthermore, EBF had lower surface roughness values among all bulk‐fill composite groups.…”
Section: Discussionmentioning
confidence: 74%
“…The physical, mechanical, and aesthetic characteristics of the restorative materials used are expected to match those of the dental tissues and enamel surfaces they come into contact with (de Souza Ferreira, Carpena Lopes, & Narcisco Baratieri, 2004). As the surface roughness of a restoration decreases, it shows better cosmetic appearance, lower susceptibility to staining, greater wear resistance, and lower risk for plaque accumulation, microleakage and secondary caries, overall contributing to periodontal health (Aytac et al, 2016; Karatas, Gul, Gündoğdu, & Iskenderoglu, 2020). In the present study, the effects of different polishing systems on surface roughness of various composites were assessed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the measurements made with an AFM device and a profilometer have been reported in some studies. This was attributed to the ability of AFM devices to provide images with higher resolution and more precise measurements (Karatas et al, 2020). Researchers have noted that profilometers alone cannot fully characterize the complex structure of the surface and therefore, more valid predictions on clinical performance can only be made when a profilometer is used in combination with AFM and SEM (Erdemir, Sancakli, & Yildiz, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the literature, no statistically significant difference was observed in color change values between the two bleaching systems in the present study because although the peroxide concentration of the at‐home bleaching agent was low, long exposure time and the use of bleaching trays and reservoirs increased bleaching efficacy, whereas the in‐office bleaching agent showed a strong whitening effect due to its high peroxide concentration (Carlos et al, 2019; Machado et al, 2016; Mounika, Mandava, Roopesh, & Karri, 2018). Many studies have shown that increased surface roughness is a determining factor for plaque accumulation on the teeth and restorative or prosthetic materials and discoloration of teeth (Karatas, Gul, Gündoğdu, & Iskenderoglu, 2020; Lu, Roeder, Lei, & Powers, 2005; Porwal, Khandelwal, Punia, & Sharma, 2017). In a study by Vieira‐Junior, Vieira, Glaucia‐Maria‐Bovi Ambrosano, and Aguiar (2018), the correlation between alteration of enamel roughness and tooth color was examined and the greatest color change (Δ E ) was observed in the group with the greatest increase in enamel roughness.…”
Section: Discussionmentioning
confidence: 99%